Preparation of ferrite layers by electrophoretic deposition / Hee Ay Ching - Hee, Ay Ching (2012)
Nickel zinc ferrite and magnesium copper zinc ferrite powders with average particle size about 22.7 nm and 26.6 nm respectively were synthesized by water-in-oil microemulsion technique. The coercivity values for magnesium copper zinc ferrite and nickel zinc ferrite were 126 Oe and 25.5 Oe respectively which indicates soft ferromagnetic behaviour. A colloidal suspension of the fine ferrite powder in ethanol was prepared. Phosphate Ester (PE) was added to the suspension as charging agent, Poly Vinyl Butyral-co-vinyl-alcohol-co-vinyl acetate (PVB) as binder and Poly Ethylene Imine (PEI) as dispersant. The effect of the charging agent on the stability of the ferrite suspension was improved by analyzing the pH, conductivity and zeta potential of the suspension. EPD process was carried out from the most stable ferrite suspension. The applied voltage, the types of electrode materials, the electrode separation distance and the concentration of the powder in the suspension were investigated in order to obtain high quality ferrite layers. Field emission scanning electron micrographs for both sintered nickel zinc ferrite and magnesium copper zinc ferrite layers exhibit a homogeneous film composed of needle-like crystal structure. X-ray diffraction and energy dispersive x-ray spectroscopy confirmed the composition of the ferrite layers formed. Atomic force microscope and magnetic force microscope have been employed to differentiate between magnetic and non magnetic phases in ferrite layers. iii